Effect of Etiology of Craniovertebral Junction Instability on Clinical Characteristics, Course, and Outcomes in Patients Undergoing Occipitocervical Fusion: A 63 Patient Cohort. (16th November 2020) - Prasad, Nikil; Shlobin, Nathan A; Azad, Hooman; Mitra, Akash; Hopkins, Benjamin; Cloney, Michael; Dahdaleh, Nader S
Abstract: INTRODUCTION: The craniovertebral junction(CVJ) is an intricate interface between the cranium and the cervical spine through which many vital structures pass. CVJ instability can arise for several reasons including rheumatoid arthritis, blunt force trauma, and tumor mass effect. Instability at this joint can cause pain, neurologic symptoms, and in some cases death due to brainstem impingement. CVJ instability is commonly corrected by performing an occipitocervical fusion (OCF). It is currently poorly understood how different etiologies of CVJ instability impact clinical presentation, course, and outcomes following an OCF. METHODS: A retrospective chart review was conducted to collect demographic and clinical data on consecutive patients at our institution that underwent OCF for all causes of CVJ instability. The Nurick scale was used as a metric of neurologic status preoperatively and at follow-up. O-C2 and C2-C7 Cobb angles were measured from pre- and postoperative radiographs. RESULTS: In our 63-patient cohort, three unique etiologies of CVJ instability were identified: rheumatoid arthritis (16 patients), blunt trauma (17 patients), malignancy (9 patients). Those with rheumatoid arthritis had increased preoperative O-C2 kyphosis compared to the general cohort ( P = .001), more vertebral segments surgically fused ( P = .047), and worse neurologic status at last clinical follow-up ( P = .047).Those with blunt trauma had fewer vertebral segments surgically fused ( P = .015). Those with malignancy had better preoperative neurologic status ( P = .047). All groups had similar neurologic status and radiographic angle changes as compared to the general cohort. There were similar instances of post-operative dysphagia and dysphonia across all groups. CONCLUSION: We demonstrate varying etiologies of CVJ instability have differing pre- and postoperative characteristics. First, those with RA are more likely to present with O-C2 kyphosis and have worse neurologic status at last follow-up. Second, those with blunt trauma are likely to require fewer segments to be fused to achieve stability. Third, those with malignancy are likely to have better neurologic function preoperatively. As such, the etiology of CVJ instability must be considered during preoperative, operative, and postoperative care planning.